Increasing Student Awareness of the School Environment Through the Adiwiyata Program - Anggraini, Vera Duwi; Widodo, Widodo (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aims to assess the extent to which the Adiwiyata Program has increased student awareness of cleanliness, sustainability, and environmental management through various activities involving the entire madrasa community. Methodology: This research employed qualitative methods with a case study design. Data collection involved field observations, interviews with madrasah principals, teachers, Adiwiyata administrators, and students, as well as documentation. Data analysis followed the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Main Findings: The Adiwiyata program improves students' hygiene habits, waste sorting, plant care, and the implementation of the 7K culture. Teachers and students actively participate in green house activities, waste management, and crafting from used materials. Key challenges include low discipline among elementary school-aged students, a lack of sanitation facilities, and a lack of hygiene habits at home. Solutions are implemented through group guidance, additional self-development hours, and financial support. Novelty/Originality of this study: This study provides a detailed overview of the process of developing environmental awareness in elementary school students through a consistent, sustainable program involving the entire school community. The findings illuminate the real challenges at the early childhood level and offer implementation strategies that can serve as models for other schools to strengthen Adiwiyata-based environmental education.